2020
DOI: 10.1017/mor.2020.37
|View full text |Cite
|
Sign up to set email alerts
|

Wining and Dining Government Officials: What Drives Political Networking in Chinese Private Ventures?

Abstract: Managerial networking with political actors has long been recognized as a crucial co-option strategy to navigate the challenging institutional environment in emerging economies. However, we know much less about what drives the variation of political networking investment by private ventures. Drawing on resource dependence theory, we unpack the dyadic business-government relations and identify the key organizational and environmental factors that shape the power dependence relationships between private ventures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…The ability to identify production and business model problems is difficult to acquire from the market (Saemundsson & Candi, 2017). However, with connection to other firms, the focal corporation can gather ‘timing, relevance, and quality of information’ through informal channels (Zhang, Sun, & Qiao, 2020). This approach encourages firms' willingness to engage in pollution prevention eco‐innovation by allowing focal firms to better detect business and production threats without compromising SEW (Chrisman et al, 2015).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The ability to identify production and business model problems is difficult to acquire from the market (Saemundsson & Candi, 2017). However, with connection to other firms, the focal corporation can gather ‘timing, relevance, and quality of information’ through informal channels (Zhang, Sun, & Qiao, 2020). This approach encourages firms' willingness to engage in pollution prevention eco‐innovation by allowing focal firms to better detect business and production threats without compromising SEW (Chrisman et al, 2015).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Consistent with these arguments, an emerging body of empirical work has shown that political ties can have an insignificant (Okhmatovskiy, 2010; Sheng et al, 2011) or even negative impact on firms' financial performance (Fan et al, 2007; Hadani & Schuler, 2013). Given such findings, recent studies have underscored “the necessary costs of such linkage” (Zhang, Marquis, & Qiao, 2016, p. 1307) and noted that it is a “rational, strategic choice (rather) than a necessity” for firms to establish political ties (Zhang et al, 2020, p. 1085).…”
Section: Conceptual Developmentmentioning
confidence: 99%
“…The benefits acquired from political ties may cause senior executives to overemphasize them and downplay the role of market mechanisms (Albino‐Pimentel et al, 2018). Thus, they may divert managerial attention to searching for ways to maintain and extend their political ties, distracting them from operations management (Wang et al, 2021; Zhang et al, 2020; Zhang, Marquis, & Qiao, 2016). Such a focus of top executives will decrease the search for cutting‐edge operational technologies or practices, leading to lower operational efficiency.…”
Section: Conceptual Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese companies are more likely to use implicit political networking as a way to take advantage of certain informal institutions (e.g. Guanxi) because of the underdeveloped formal mechanisms in facilitating government–business interactions (Wang et al , 2003; Zhang et al , 2020). Therefore, the validity of the results of company-level tax research in China is questionable in the absence of consideration of corporate political connections (He et al , 2019b).…”
Section: Literature Reviewmentioning
confidence: 99%